Redes sociais na participação democrática: desafios contemporâneos na efetivação dos direitos do e-cidadão - Bezerra, Eudes Vitor (2016)
This thesis aims to demonstrate how social networks as a new instrument of democratic participation, influence current manifestations, events and what are the current challenges for realization of the e-citizen rights. We intend to present as public participation has taken place through new forms and using new tools such as "social networks". Therefore, a historical, comparative and bibliographical analysis, it is the thesis of this to understand the role of social networks in the context of change, and which the contemporary challenges to the realization of the e-citizen rights and Cyber Democracy. Proposing at the end, the inclusion of the subject "Citizenship and social networks" in high school, through amendment of Resolution SE 81 of 16-12-2011, the State of São Paulo, and the vote, approval and sanction of BS No 129/2010, which validates digital signatures in the popular initiative bills as a way to reduce the digital exclusion and strengthen democratic participation through social networks